2013
DOI: 10.1371/journal.pone.0059370
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Culture Supernatant of Bifidobacterium breve CNCM I-4035 Decreases Pro-Inflammatory Cytokines in Human Dendritic Cells Challenged with Salmonella typhi through TLR Activation

Abstract: Dendritic cells (DCs) constitute the first point of contact between gut commensals and our immune system. Despite growing evidence of the immunomodulatory effects of probiotics, the interactions between the cells of the intestinal immune system and bacteria remain largely unknown. Indeed,, the aim of this work was to determine whether the probiotic Bifidobacterium breve CNCM I-4035 and its cell-free culture supernatant (CFS) have immunomodulatory effects in human intestinal-like dendritic cells (DCs) and how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 51 publications
7
77
0
1
Order By: Relevance
“…As with dendritic cells, IEC-6 can also express TLR-9. Recent studies have shown that Bifidobacterium can secret the TLR-9 ligand, unmethylated CpG DNA fragments (Bermudez-Brito et al, 2012, 2013. The above information and the results of this study suggest that the supernatant of Bifidobacterium may bind to TLR-9 in IEC-6 through a non-methylated CpG DNA fragment, activating the TLR-9 pathway of the IEC-6 cells and NF-κB, and thereby causing the generation of miRNA-146a.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…As with dendritic cells, IEC-6 can also express TLR-9. Recent studies have shown that Bifidobacterium can secret the TLR-9 ligand, unmethylated CpG DNA fragments (Bermudez-Brito et al, 2012, 2013. The above information and the results of this study suggest that the supernatant of Bifidobacterium may bind to TLR-9 in IEC-6 through a non-methylated CpG DNA fragment, activating the TLR-9 pathway of the IEC-6 cells and NF-κB, and thereby causing the generation of miRNA-146a.…”
Section: Discussionsupporting
confidence: 59%
“…Bermudez-Brito et al (2013) found that Bifidobacterium supernatant can upregulate TLR-9 in intestinal dendritic cells, thereby activating the TLR pathways to regulate the body's innate immune response and inflammation (Taganov et al, 2006). As with dendritic cells, IEC-6 can also express TLR-9.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, our research group [55] co-incubated intestinal-like human DCs from cord blood CD34+ progenitor cells [56] with B. breve CNCM I-4035 or its cell-free supernatant (CFS), S. typhi or a combination of these treatments for 4 h. These treatments upregulated TLR-9 gene transcription. In addition, CFS was a more powerful inducer of TLR-9 expression than were the probiotic bacteria in the presence of S. typhi.…”
Section: Dendritic Cellsmentioning
confidence: 99%